An Evaluation Of Proposed Readability Formula In Malay Language - Mohamad Zawawi, Nur Amalina; Hisham, Syariffanor; Zakaria, Mohd Hafiz; Sainawan, S. S. (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Based on discussions with counsellor at Kolej Komuniti Jasin, Melaka, we have found that most of young adults in Malaysia particularly students at Higher Education Institutions and TVET Colleges have a poor learning problem especially in reading and writing. This paper presents findings driven from an evaluation conducted in a field study on reading assessment using SPIKE. SPIKE or Sistem Kebolehbacaan Bahasa Melayu is a Malay readability test tool that can evaluate the readability competencies of a reader. SPIKE allows the teachers to screen students who may struggle to read and help to formulate action plans for specific forms of learning and interventions to enable them to obtain their academic qualifications. Results obtained has indicated that the tool can benefit general public as well as people with reading difficulties (including dyslexics) in measuring their reading competencies and the readability level of a reading material whether it is suitable for the reader’s age. For future work, it is expected that this tool will help to increase the accuracy of measuring reading competencies of readers and be able to assist readers who have difficulties in reading by knowing the score level of their reading materials in Malay. It also can benefit them in upgrading young adults’ academic performance.